Functions and Behudapanti

Algebra Level 4

A non-zero polynomial f f satisfies

f ( f ( x ) ) = ( x + x 2 + x 3 + ) f ( f ( f ( x ) ) f(f(x)) = (x + x^2 + x^3 + \ldots) f(f(f(x))

for all 0 < x < 1 0 < x < 1 . Determine the smallest value of f ( x ) 2 + x f(x)^2 + x where x x ranges over all real numbers.


The answer is 0.75.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Arturo Presa
Oct 23, 2015

The equation f ( f ( x ) ) = ( x + x 2 + x 3 + ) f ( f ( f ( x ) ) f(f(x)) = (x + x^2 + x^3 + \ldots) f(f(f(x)) can be rewritten in the form f ( f ( x ) ) = x 1 x f ( f ( f ( x ) ) f(f(x)) = \frac{x}{1-x}f(f(f(x)) , or, equivalently, in the form ( 1 x ) f ( f ( x ) ) = x f ( f ( f ( x ) ) . ( 1 ) (1-x)f(f(x)) = x f(f(f(x)).\:\:\:\:\:\:\:\:\:\:\:\:(1) Let us assume that the degree of the polynomial f ( x ) f(x) is n . n. Using that for any two polynomials g ( x ) g(x) and h ( x ) h(x) the degree of the polynomial g ( h ( x ) ) g(h(x)) is the product of the degrees of g ( x ) g(x) and h ( x ) , h(x), we obtain that the left side of (1) is a polynomial of degree n 2 + 1 n^{2}+1 and the right side is a polynomial of degree n 3 + 1 n^{3}+1 . Then n 2 + 1 = n 3 + 1 n^{2}+1=n^{3}+1 . Therefore, n = 1 n=1 or n = 0. n=0. If n = 0 , n=0, then f ( x ) f(x) will be a constant polynomial and the equation (1) will imply that f ( x ) = 0 f(x)=0 for all x , x, but f ( x ) f(x) must be a non-zero polynomial, so n = 1. n=1. It means that f ( x ) = a x + b f(x)=ax+b where a 0. a \neq 0. Then formula (1) yields a 2 x 2 + ( a b b + a 2 ) x + ( a b + b ) = a 3 x 2 + ( a 2 b + a b + b ) x . -a^{2} x^2+(-a b-b+a^{2}) x +(ab+b) =a^{3} x^{2}+(a^{2} b+ab+b)x.

Making corresponding coefficients equal, we get the following equations: a 2 = a 3 , -a^{2}=a^{3}, a b b + a 2 = a 2 b + a b + b , -a b-b+a^{2}=a^{2}b+ab+b, a b + b = 0. a b + b =0. Since a 0 a\neq 0 then we have to consider only solution of this system of equation, which is a = 1 , a=-1, b = 1 b=1 . Therefore, f ( x ) = x + 1. f(x)=-x+1. Then f 2 ( x ) + x = ( x + 1 ) 2 + x = x 2 x + 1 = ( x 1 2 ) 2 + 3 4 . f^{2}(x)+x=(-x+1)^2+x=x^{2}-x+1=(x-\frac{1}{2})^2+\frac{3}{4}. The minimum value of this expression is 3 4 = 0.75 \frac{3}{4}=0.75 , and it attained at x = 1 2 . x=\frac{1}{2}.

Another great solution! Thank you so much!

Pi Han Goh - 5 years, 6 months ago

Log in to reply

Thank you @Pi Han Goh

Arturo Presa - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...